Novel and holistic approaches are required to realize allelopathic potential for weed management. Issue 4 (21st April 2023) - Hickman, Darwin T.; Comont, David; Rasmussen, Amanda; Birkett, Michael A.
Abstract: Allelopathy, that is, plant–plant inhibition via the release of secondary metabolites into the environment, has potential for the management of weeds by circumventing herbicide resistance. However, mechanisms underpinning allelopathy are notoriously difficult to elucidate, hindering real‐world application either in the form of commercial bioherbicides or allelopathic crops. Such limited application is exemplified by evidence of limited knowledge of the potential benefits of allelopathy among end users. Here, we examine potential applications of this phenomenon, paying attention to novel approaches and influential factors requiring greater consideration, with the intention of improving the reputation and uptake of allelopathy. Avenues to facilitate more effective allelochemical discovery are also considered, with a view to stimulating the identification of new compounds and allelopathic species. Synthesis and Applications: We conclude that tackling increasing weed pressure on agricultural productivity would benefit from greater integration of the phenomenon of allelopathy, which in turn would be greatly served by a multi‐disciplinary and exhaustive approach, not just through more effective isolation of the interactions involved, but also through greater consideration of factors which may influence them in the field, facilitating optimization of their benefits for weed management. Abstract : Allelopathy holds promise as an alternative method for weed management, but its application is hampered by limited methodological development and ecological context. This paper therefore considers ecological and evolutionary context for the phenomenon which can aid its further discovery and development, before exploring more holistic approaches and underutilized applications which could benefit agricultural weed management.